Identification and Validation of Damage Parameters for Elasto-Viscoplastic Chaboche Model - AMBROZIAK, A. (Engineering Transactions, 2007)
The aim of the paper is to propose an improved procedure of damage material parameters identification of the Chaboche model, coupled with the concept of isotropic damage model proposed by Amar and Dufailly [2]. The proposed approach has been implemented into subroutines of the FE MSC.Marc code, as the user’s viscoplastic subroutine UVSCPL, and has been used to perform FE static and dynamic computations. The paper gives a brief description of the Chaboche model including damage. The results are also presented of FE dynamic analyses using the respective UVSCPL subroutine. Analyses have been made for the nickelbased superalloy INCO718 and for steel. The numerical examples prove that the proposed identification approach is effective and the numerical implementation is correct.